Community Participation Provides Hydrological Environmental Services In the Watershed Area - Sukwika, Tatan (Universitas Sahid, 2023)
The extent of critical and potential critical land in the Kambaniru watershed has encouraged community perceptions where management of land and forests in the watershed-based area of community empowerment is an important effort. To be able to achieve a good Kambaniru watershed condition, the behavior and activities of land and forest utilization by the community must comply with the principles of soil and water conservation. High population growth rate and followed by pressure on land has the potential to create new social problems in the form of poverty. On the other hand, the large potential of people who are willing to provide hydrological environmental services in watershed areas can be used as government investment. Therefore, opportunities for community participation need to be managed through an incentive approach through a cost-sharing mechanism. The overall objective of this study is to formulate a cost-sharing regression model of hydrological environmental services; to analyze the value of hydrological benefits for households at the upstream level in the Kambaniru watershed area, and assess the condition of community poverty levels based on pressure on land in the Kambaniru watershed area. This study concludes the formulation of the cost-sharing regression model of hydrological environmental services in the Kambaniru watershed area can explain the condition of the amount of water use and water requirements for households. The condition of population poverty is triggered by high pressure and dependence on land and forests. The recommendation is that farmer household should be given hydrological benefit compensation and lending without interest.